Development of a bioavailable boron-containing PI-103 Bioisostere, PI-103BE. Issue 14 (15th July 2020) - Luo, Lan; Zhong, Qiu; Guo, Shanchun; Zhang, Changde; Zhang, Qiang; Zheng, Shilong; He, Ling; Wang, Guangdi
Graphical abstract: Novel PI-103 bioisostere, PI-103BE (9 ), displays higher bioavailability than PI 103 (7) in vivo . Abstract: PI-103 (7 ) is a potent dual phosphatidylinositol 3-kinase (PI3K)/mTOR inhibitor, but its rapid in vivo metabolism hinders its further clinical development. To improve the bioavailability of PI-103, we designed and synthesized a PI-103 bioisostere, PI-103BE (9 ) in which the phenolic hydroxyl group of PI-103 was replaced by a boronate, a structural modification known to enhance bioavailability of molecules containing phenolic hydroxyl moieties. In cell culture, PI-103BE is partially converted to its corresponding boronic acid (10 ) and to a lesser extent the active ingredient, PI-103. This mixture contributes to the in vitro activity of 9 that shows reduced potency compared to the parent compound. When administered to mice by oral gavage, 9 displays a significantly improved pharmacokinetic profile compared to PI-103, which shows no oral bioavailability at the same dose. Drug exposure of 9 as measured by the area under curve (AUC) value is 88.2 ng/mL*h for 7 and 8879.9 ng/mL*h for 10 . When given by intraperitoneal injection (IP), the prodrug afforded an AUC of 32.3 ng/mL*h for 7 and 400.9 ng/mL*h for 10, compared to 9.7 ng/mL*h from PI-103 injection. In plasma from both pharmacokinetic studies, 9 is fully converted to 10 and 7, with the boronic acid metabolite (10 ) displaying antiproliferative activities comparable to 9, but weaker than 7 . The boronic bioisostere of PI-103 thus offers an improved bioavailability that could be translated to in vivo efficacy of PI-103.